Colonialism and Education: English Language Education in Sri Lanka - Fernando, Marie Clare (Richtmann Publishing, 2012)
The English Language was introduced to Sri Lanka by the British colonial rulers at the beginning of the 19thcentury. Since then the existence of the people of Sri Lanka changed significantly together with the valuesand attitudes towards life. Independence gained in the 20th century did not have a speedy recovery on thedamages done to the thinking patterns of the people; making the languages people used as a wedge. Themuch debated ‘Sinhala Only’ policy in 1952 paved the way for the Sinhala educated mass to come to theadministrative strata of the country in the post colonial times. Yet, English was not dethroned; it enjoyedthe prestige it used to have. The intension of this paper is to discuss the efforts taken to remove the colonialmind set from the people of Sri Lanka while opening doors for globalization through English Languageeducation. The variety of English called Sri Lankan English emerged clandestinely; even the users of thisvariety of English were unaware of its existence. The new found identity can be the stepping stone inplacing English language at its right place, and acquiring the skills and knowledge necessary to competewith the global standards.